Marginal and Interaction Effects in Ordered Response Models - Debdulal Mallick (Economics and Econometrics Research Institute (EERI), 2009)
In discrete choice models the marginal effect of a variable of interest that is interacted with another variable differs from the marginal effect of a variable that is not interacted with any variable. The magnitude of the interaction effect is also not equal to the marginal effect of the interaction term. I present consistent estimators of both marginal and interaction effects in ordered response models. This procedure is general and can easily be extended to other discrete choice models. I also provide an example using household survey data on food security in Bangladesh. Results show that marginal effects of interaction terms are estimated by standard statistical software (STATA® 10) with very large error and even with wrong sign.
Keywords: C12; C25; 330; Marginal effect; interaction effect; ordered probit; discrete choice